functions and relations

Mathematics
Tutor: None Selected Time limit: 1 Day

1) Find f(g(x)) if f(x) = 3x + 1 and g(x) = x2 - 1.

2) Find g(f(x)) if f(x) = 2x – 3 and g(x) = x2 - 1.

3)Find the zeros of f(x) = 

4) Find the zeros of f(x) = 

Sep 16th, 2014

1) Replace x= x^2 - 1 in f(x)

f(g(x)) = f(x^2 - 1) = 3 ((x^2)-1) + 1

                             = 3 x^2 -3 + 1  distributing 3 inside the parenthesis

                             = 3 x^2 - 2  

2) Replace x= 2x-3 in g(x)

 g(f(x) = g(2x-3) = (2x-3)^2 - 1

                          = (2x)^2 - 2(2x)(3) + 3^2 - 1       because (ax-b)^2 = a^2x^2 - 2 abx + b^2

                          = 4 x^2 - 12x + 9  - 1

                           = 4 x^2 - 12x + 8           you can divide by 4 to simplify

                           = x^2 - 3x + 2

3) Zeros of a function f(x) = 0 but you need to know the function.

   Ex: f(x)  = 3x + 1 = 0

                    3x +1 -1 = 0 - 1

                             3x = -1     then dividing by 3 both sides

                                x= -1/3  is the zero of the function 

  Ex: f(x) = 2x - 3 = 0

                   2x - 3 + 3 = 0 + 3   

                              2x = 3          then dividing by 2

                                x = 3/2  is the zero of the function.

Sep 16th, 2014

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Sep 16th, 2014
...
Sep 16th, 2014
Dec 6th, 2016
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer